Gender balance in teaching awards: evidence from 18 years of national data. Issue 4 (3rd July 2016) - Marchant, Teresa; Wallace, Michelle
ABSTRACT: Gender implications of nationally competitive teaching awards were examined to determine whether women receive sufficient accolades, given their dominant position in university teaching. Quantitative methods and secondary data provided objective analysis of teaching awards for Australian universities, for an 18-year data set with 2046 units of analysis. Results indicate that women were over-represented in lower-level citations and under-represented in higher-level awards. Women did not dominate, particularly the highly prestigious Prime Minister's award, where men constituted 65%. Policy and management implications include that universities could review the gender balance in their teaching award processes and set goals as internal support is a springboard to national awards. Groups of the same gender could be encouraged to work together at the highest levels to overcome individualistic, competitive barriers. National teaching award applications could be gender blind, at least for the higher levels. There are no clear trends towards a better gender balance, possibly because there has been a very limited gender spotlight on the awards at any level of policy and management.